Analisis Kapasitas Tampungan Waduk Sungai Paku Kecamatan Kampar Kiri Kabupaten Kampar - Andika Satria Agus; Mudjiatko Mudjiatko; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Sungai Paku reservoir built by the Public Works Department of Riau Province in Sungai Paku, Kampar Kiri subdistrict, Kampar district used as a irrigation water source to irrigate 373 hectares of agricultural land in the Regional Irrigation (DI) Sungai Paku and is planned as a raw water source for the population in surroundings. Base contours Sungai Paku reservoir are needed to determine the reservoir capacity curve. This curve expressing the relation of elevation, area, and volume in Sungai Paku reservoir. Water availability in Sungai Paku reservoir is calculated by the method of Mock while water loss is calculated from the outflow through the outlet, evaporation, and raw water needs of the population. The results showed the largest water availability occurred in April in the amount of 2.5217 m3 / sec and the largest water loss occurs in December in the amount of 0.7150 m3 / sec. Water shortages occur in August amounted to 0.1087 m3 / sec or in units of volume (m3) will be amounted to 291,124.914 m3 with the life storage capacity of the Sungai Paku reservoir of 2,497,988.579 m3 Sungai Paku reservoir able to cover water shortages occur and can be used as a raw water source for the population in surroundings.Keyword : Reservoir, storage capacity, water balance